THE ACTIVE LAERNING ACTIVITIES IN THE NEXT NORMAL ERA TO ENHANCE THE COMPETENCY OF PHETCHABURI PROFESSIONAL TEACHER FOR STUDENTS TEACHER OF PHETCHABURI RAJABHAT UNIVERSITY - Romphruek, farida; Phueakbuakhao, Wipavanee; Sala, Wanlaya (Journal of MCU Phetchaburi Review, 2023)
This research aimed to develop active learning activities in the next normal era and to develop Phet innovator teacher skills of Phetchaburi Rajabhat University students by using active learning activities in the next normal era. The sample group were 125 Social Studies major students in the first year to third year who studied in Practicum in Profession of Teaching course. The research instruments were 1) A course syllabus of Practicum in Profession of Teaching taught by active learning, 2) An observation form of Phetchuburi Professional Teacher skills with 5 skills. The data were analyzed by using mean (), standard deviation (S.D.) and content analysis. The findings appeared that five steps of the active learning activities to develop Phetchuburi Professional Teacher skills of Phetchaburi Rajabhat students in the next normal era consisted of 1) Seek information, 2) See all problems, 3) Seek diversity, 4) Find all-round answers, 5) Find appropriate conclusions. The active learning method was also integrated with other learning activities systems such as Google classroom, other applications and digital tools. After using active learning in the next normal era, the students’ skills were at a high level (=4.28). When considered in each skill, it was found the mean of collaboration skill was the highest (=4.62), the communication skill (=4.38), the creative skill (=4.26) and information technology skills (=4.14) were ranked respectively, while the mean of critical thinking skills were the lowest (=3.66). Keywords : Active Learning Activities, Next normal Era, Phetchuburi Professional Teacher